2020
DOI: 10.1096/fj.201901416rr
|View full text |Cite
|
Sign up to set email alerts
|

Novel roles of dense granule protein 12 (GRA12) inToxoplasma gondiiinfection

Abstract: are contributed equally to this work. AbstractDense granule protein 12 (GRA12) is implicated in a range of processes related to the establishment of Toxoplasma gondii infection, such as the formation of the intravacuolar network (IVN) within the parasitophorous vacuole (PV). This protein is also thought to be important for T. gondii-host interaction, pathogenesis, and immune evasion, but their exact roles remain unknown. In this study, the contributions of GRA12 to the molecular pathogenesis of T. gondii infec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
60
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 34 publications
(62 citation statements)
references
References 58 publications
0
60
2
Order By: Relevance
“…Intriguingly, the phosphorylation level of GRA2 was detected to be up-regulated significantly in the comparison group of PE vs. JI, which suggested that phosphorylation may be one of the important mechanisms in mediating the function of GRA2. Surprisingly, both GRA3 and GRA12 were identified with enhanced phosphorylation level in this study yet were shown to be dispensable for the lytic cycle of T. gondii in vitro, however, they play essential roles in acute infection of T. gondii in vivo (Craver and Knoll, 2007;Rommereim et al, 2016;Fox et al, 2019;Wang et al, 2020). The explanation of this discrepancy may be that GRA3 and GRA12 do not play their roles independently in the lytic cycle process of tachyzoites but interdependently, just as other GRA proteins (Rommereim et al, 2016).…”
Section: Discussioncontrasting
confidence: 54%
“…Intriguingly, the phosphorylation level of GRA2 was detected to be up-regulated significantly in the comparison group of PE vs. JI, which suggested that phosphorylation may be one of the important mechanisms in mediating the function of GRA2. Surprisingly, both GRA3 and GRA12 were identified with enhanced phosphorylation level in this study yet were shown to be dispensable for the lytic cycle of T. gondii in vitro, however, they play essential roles in acute infection of T. gondii in vivo (Craver and Knoll, 2007;Rommereim et al, 2016;Fox et al, 2019;Wang et al, 2020). The explanation of this discrepancy may be that GRA3 and GRA12 do not play their roles independently in the lytic cycle process of tachyzoites but interdependently, just as other GRA proteins (Rommereim et al, 2016).…”
Section: Discussioncontrasting
confidence: 54%
“…To achieve this, each mouse was infected i.p. with 10 3 tachyzoites (five mice/strain), and five days later, the parasite burden in the peritoneal fluid was examined by plaque assay as described previously [22]. Briefly, mice were humanely sacrificed, and peritoneal cells were harvested by lavage with phosphate buffered saline (PBS) containing 1% FBS.…”
Section: Optimization Of the Vaccination Dosementioning
confidence: 99%
“…Then 100 µL freshly liberated parasites were used to infect confluent HFF monolayers maintained in RPMI1640 medium for seven days. Then, T. gondii-infected HFFs were fixed and stained, and the sizes and numbers of plaques formed by the growing tachyzoites were determined using the plaque assay as described previously [22].…”
Section: Optimization Of the Vaccination Dosementioning
confidence: 99%
“…Corticosteroid (dexamethasone) immune suppressed or IFN‐γ −/− mice infected with parasites lacking GRA12 I/II succumb to infection. Despite its implication in modulation of IFN‐γ mediated immune responses, the GTPase effectors do not assemble on the vacuoles of parasites without GRA12 (Fox et al, 2019; Wang et al, 2020). GRA7/II together with other PVM associated GRAs were found to make up the cyst wall and membrane and shown to be important for cyst formation (Guevara, Fox, & Bzik, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Once phosphorylated, IRGs are unable to hydrolyse GTP and cannot form oligomers, hence IRG loading onto the PVM is disabled (Steinfeldt et al, 2010). GRA12, on the other hand, resides within the PV and contributes to both parasite virulence and establishment of chronic infection through modulation of IFN‐γ mediated immune responses without involving the GTPase effectors (Fox et al, 2019; Wang et al, 2020).…”
Section: Introductionmentioning
confidence: 99%